Is There a New Vision for Maghreb Economic Integation? Volume 2. Annex - World Bank (Washington, DC, 2014)
This report on the new vision for Magreb economic integration argues that assessing the benefits from regional integration can best be done in the context of the broader issues of economic integration in the world economy and more specifically with the main trading partner, the European Union. Based on empirical evidence the paper finds that there is limited potential for intraregional merchandise trade integration in the Maghreb. The report also alerts that benefits from deeper economic integration are no means automatic. Several worldwide studies have argued that weaknesses in the investment climate not only hinder a country's imports and inward foreign direct investment, they also deter exports from enterprises operating in the domestic economy (World Bank, 2005). Service liberalization requires complementary policies and effective regulation, ranging from prudential regulation to pro-competitive regulation in telecommunications. The concluding message emerging from the analysis is that a strategy focusing on service sector and investment climate reforms aimed at facilitating market competition and contestability would improve growth, trade and investment performance in the Maghreb, bringing greater economic gains than would be derived from merchandise trade liberalization alone. The report is structured as follows. The first chapter examines the prospects of regional integration based on merchandise trade liberalization. It does so by performing a detailed quantitative analysis of Maghreb's trade and investment patterns and performance. The chapter also assesses Maghreb countries' trade and investment potential, drawing on panel trade and investment gravity models. The second chapter identifies policy barriers, relative performance and progress made by Maghreb countries in investment climate and service sector policy reforms. To allow for cross-country comparability, the report draws on the methodology developed by the European Central Bank for Reconstruction and Development (EBRD) to construct policy reform indexes for the Maghreb countries. The third chapter aims at estimating the economic gains from deeper and wider integration. The final section of the report summarizes the main conclusions and policy implications drawn from the analysis.